2013
DOI: 10.1155/2013/382485
|View full text |Cite
|
Sign up to set email alerts
|

Successful Obliteration of a Pseudoaneurysm from Post-CEA Repair Secondary to a Pruitt-Inahara Shunt Using a Stent Graft

Abstract: Pseudoaneurysms of the carotid artery are very uncommon complications following carotid endarterectomy. Pseudoaneurysms are usually caused by any kind of blunt injury or trauma during carotid artery surgery. CEA has become an increasingly more common vascular surgery performed in the United States. The standard of treatment for a carotid PA has been open surgical repair with excision of the defect and then a graft reconstruction of the artery. Advancements in endovascular intervention have helped to make it a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the literature review process, we found 29 papers for an overall amount of 39 patients with post-CEA PA treated by an endovascular approach since 2000 (Table 1). Twenty were patients from isolated case reports, 4,5,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] the remaining were extracted from small case series dealing with extracranial carotid aneurysms regardless of the etiology. 3,8,[26][27][28][29][30][31][32] Overall mortality was 2.6% (1 for myocardial infarction), and neurological complications occurred in 5.1% (2 TIAs).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review process, we found 29 papers for an overall amount of 39 patients with post-CEA PA treated by an endovascular approach since 2000 (Table 1). Twenty were patients from isolated case reports, 4,5,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] the remaining were extracted from small case series dealing with extracranial carotid aneurysms regardless of the etiology. 3,8,[26][27][28][29][30][31][32] Overall mortality was 2.6% (1 for myocardial infarction), and neurological complications occurred in 5.1% (2 TIAs).…”
Section: Discussionmentioning
confidence: 99%
“…2 PAs of the internal carotid artery distal to the surgically exposed zone are very rare; the main etiology in such cases has been attributed to Pruitt-Inahara shunt balloon inflation. 3,4 This device is commonly used during CEA to provide blood flow to the brain whenever intolerance to vessel clamping occurs. A balloon is inflated in both the common and the internal carotid artery to fix the device during endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In the first one, 3 the authors reported that, considering the small size of the PA which remained unchanged during follow-up, they decided against taking an invasive approach. They also suggested 3 explanations for PA formation after CEA: distal balloon overinflation, normal balloon inflation in a previously damaged area of the artery, and local dissection followed by PA formation.…”
Section: Discussionmentioning
confidence: 99%